Histochemical observations on circumvallate papillae and associated glands in tongue of sheep - PAWAR, H S; SINGH, JASWANT; ROY, K S (The Indian Journal of Animal Sciences, 2013)
The phosphatase in gustatory epithelium of sheep circumvallate papillae revealed site-specific histochemical localization of AKPase, ACPase and ATPase was mainly localized in taste bud cells. The presence of various phosphatases, esterases and oxidorcductascs in superficial byer of moat indicated a physiologically active stratum comeum. Papillae-associated glundular parenchyma also revealed strong activities of AKPase, ATPasc, SDH, LDH and NADPH .